2015
DOI: 10.46743/2160-3715/2015.2116
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychology’s Character Strengths in Addiction-Spirituality Research: A Qualitative Systematic Literature Review

Abstract: There is an increasing interest in the scientific study of the association between spirituality and recovery from addiction. While most of these studies have provided evidence for a possible relationship, others have explored the underlying mechanisms and meditators in the relationship. However, generally, many studies and reviews have not approached the issue within a specific theoretical framework of mainstream psychology. In an attempt to fill this gap, the review being reported here undertook a Qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
5
0
1
Order By: Relevance
“…Qualitative systematic literature reviews focus attention on the discussion and recommendations rather than quantitative results or procedures (Selvam & Sahaya, 2015). The qualitative techniques used were thematic analysis using Braun and Clarke's (2006) six phases.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative systematic literature reviews focus attention on the discussion and recommendations rather than quantitative results or procedures (Selvam & Sahaya, 2015). The qualitative techniques used were thematic analysis using Braun and Clarke's (2006) six phases.…”
Section: Methodsmentioning
confidence: 99%
“…In March 2022, the time of authoring this work, a search of the scholarly databases Google Scholar and ProQuest using the search term “Character Strengths” AND “Addiction Recovery” did not return any results looking at character strengths as a broad-spectrum strategy for strengthening addiction recovery. The results returned from this search showed existing work was limited, having focused on the specific application of a strength, for example, the use of gratitude as a means to build reserves of recovery capital to safeguard long-term recovery (White, 2008; Chen, 2017) or in how character strengths relate to a particular area of interest such as spirituality (Selvam, 2015). The present study looks at how the VIA model of character strengths can be applied as a general resource to support those in addiction recovery, with the aim of suggesting a way to appreciate the positive outcomes seen in other areas of research (Niemiec, 2019; Schutte and Malouff, 2019) to addiction recovery.…”
Section: Methodsmentioning
confidence: 99%
“…As previously mentioned, current research looking at character strengths and addiction recovery has considered them as an expression of something more abstract; for example, can spirituality in addiction be identified through character strengths (Selvam, 2015), or how the use of a single strength such as gratitude can aid recovery (Chen, 2017). This study has shown that in using the VIA character strength model as a broad-spectrum resource for people in addiction recovery, a mechanism is provided for analysing recovery in the context of an individual's positive traits, namely, their character strengths.…”
Section: Perspectivementioning
confidence: 99%
“…Within the wider social context, an extensive body of literature points to an increasing awareness of an association between spirituality and recovery from addiction (Selvam 2015:398-400). In reviewing the literature, Selvam (2015) explored whether the mediators of the association between spirituality and recovery from addiction could be identified in terms of the character strengths of positive psychology.…”
Section: Encouraging a Culture Of Recovery During Lockdownmentioning
confidence: 99%